Electrospun Polymer-Fiber Solar Cell. (9th July 2013) - Nagata, Shinobu; Atkinson, Gary M.; Pestov, Dmitry; Tepper, Gary C.; Mcleskey, James T.
Abstract : A novel electrospun polymer-fiber solar cell was synthesized by electrospinning a 1 : 2.5 weight% ratio mixture of poly[2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylenevinylene] (MEH-PPV) and [6, 6]-phenyl C61 butyric acid methyl ester (PCBM) resulting in bulk heterojunctions. Electrospinning is introduced as a technique that may increase polymer solar cell efficiency, and a list of advantages of the technique applied to solar cells is discussed. The device achieved a power conversion efficiency of η = 3.08 × 10 − 7 %. The absorption and photoluminescence of MEH-PPV nanofibers are compared to thin films of the same material. Electrospun nanofibers are discussed as a favorable structure for application in polymer solar cells.